Degradasi Seni Reduksi Kreatifitas Dalam Arus Globalisasi - Iksan, Nur (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2011)
As human beings that be dynamic creatures, they should not compromise or ended by neutralized from the authenticity offering from the outside. They should optimize their having potential to reveal the reality and they involvement in any process that they must be a subject of the process if they want to ben gebuine self.This portion will put them on the holistic of knowledge that became the foundation for life. This knowledge as a foundation for the improvement of the meaning of life into a personal selft and forming themselves freely and be aware of his actions. A konswensi to be faced with the choice of putting the authority that based on autonomous, and appreciation for the confidence with which to create a form of human responsibility for the existence. Humans created to â€œbe authenticâ€. there are two elements of human to act creative. They are the productive capacity and the ability to rekonstruktif. every human being has the potential for resulting in literary works, independence be important factor fr themselves with â€œintactâ€ and put the position by way of productivity in order to meet their needs. Creativity (the essence of art) this boils down to whether itâ€™s the creation of something that could be used by others or just for personal expression. Here the creation of a literary work does not mean he has to paint, play music, play movies, and art is actually an activity that has an important role in human life, and in some perspectives of art is one aspect that mustÂ  be fulfilled for people in need of aesthetic or beauty. As a tool for reflection and raise awareness in personal, to response any issues.Here the subjectivity has a vital role in a terms of beautiful sense that have relation with a sense of satisfaction problems in human beings, there is fundamental need and absurd in its fulfillment.Moreover, the reality of the dynamic, demanding for human to always be example, the primordial man with several tolls in the ritual that aimed to worshiping the gods. The appearance of gods as projections is be the substances that embodiment of sublime everything that in needs are absurd. That is something similar that can be found in every human being in compliance with the terms that are beautiful. keywords : creativity, art,authentic.